Pseudo-Code Attack (PCA) in Software Engineering (International Journal of Innovative Research in Computer Science & Technology, 2021)
Software development has been more  important in recent technological advancements in both  hardware and software. The creation of scripting  languages is critical to the development of software. The  development of programming languages is applicable to  software metric calculations such as line of code, code  minimization, re-usability, and so on. Various attacks  may be carried out during the metric computation phases  in order to decrease the model parameters and delay the  software package offering. Many attacks in networks  have been discovered and avoided; this Pseudo-code assault is a new technique for boosting metric estimation  in software development. This article suggested a method  for introducing the Pseudo-code threat and detecting the  presence of the Pseudo-code assault in the code base. Estimated size and duration are key quality assurance  metrics in software development process. Software  quality is measured by the average time between failures  and the number of defects per line of code.
Keywords: Engineering; Pseudo-Code Attack; Software; Software Development